Stretch-Induced Biased Signaling in Angiotensin II Type 1 and Apelin Receptors for the Mediation of Cardiac Contractility and Hypertrophy - Seo, Kinya; Parikh, Victoria N.; Ashley, Euan A. (Frontiers in Physiology, 2020)
The myocardium has an intrinsic ability to sense and respond to mechanical load in order to adapt to physiological demands. Primary examples are the augmentation of myocardial contractility in response to increased ventricular filling caused by either increased venous return (Frank–Starling law) or aortic resistance to ejection (the Anrep effect). Sustained mechanical overload, however, can induce pathological hypertrophy and dysfunction, resulting in hypertrophy, heart failure, and arrhythmias. It has been proposed that angiotensin II type 1 receptor (AT1R) and apelin receptor (APJ) are primary upstream actors in this acute myocardial autoregulation as well as the chronic maladaptive signaling program. These receptors are thought to have mechanosensing capacity through activation of intracellular signaling via G proteins and/or the multifunctional transducer protein, β-arrestin. Importantly, ligand and mechanical stimuli can selectively activate different downstream signaling pathways to promote inotropic, cardioprotective or cardiotoxic signaling. Studies to understand how AT1R and APJ integrate ligand and mechanical stimuli to bias downstream signaling are an important and novel area for the discovery of new therapeutics for heart failure. In this review, we provide an up-to-date understanding of AT1R and APJ signaling pathways activated by ligand versus mechanical stimuli, and their effects on inotropy and adaptive/maladaptive hypertrophy. We also discuss the possibility of targeting these signaling pathways for the development of novel heart failure therapeutics.